Invasive Fungal Infection among Transplant Tourism Patients. (July 2018) - Al Salmi, Issa; Metry, Abdel Massiah; Al Ismaili, Faisal; Al Riyami, Marwa; Khamis, Feryal; al Abri, Seif
Abstract : Background: Deceased and live-related renal transplants (RTXs) are widespread approved methods throughout the world. In addition, commercial RTX has become popular in certain places driven by financial greed. Method: This is a retrospective, descriptive study was done at the Royal Hospital (RH) from 2013 to 2015. The data have been collected from the national Oman kidney transplant registry. All transplant cases retrieved were divided into two groups, Live-related-RTX performed in Oman and commercial-unrelated-RTX performed abroad. Furthermore these groups were divided into those without and those with evidence of fungal infection either in the wound or renal graft. Results: There were 198 cases of RTX, of whom 162 (81.8 %) had commercial RTX that were done abroad. In 8% of patients who had commercial RTX, IFIs were diagnosed; of these, 76.9 % underwent nephrectomy and 23.1 % continued with a functioning graft. None of the RTXs performed in RH contracted IFIs. Figure. No caption available. The most common fungal isolates were Aspergillus species including A Flavus, A. Fumigatus, A. Nidulans and A. Nigrican) followed by Zygomycetes. However, there was no evidence of fungal infection including Aspergillus outside the graft site. Computerized tomography (CT) findings showed infarction of graft, renal artery thrombosis, aneurysmal dilatation of external iliac artery, fungal ball or just presence of peri-graft collection. Of the total IFIs, 23.1% died due to septic shock and 53.8 % were alive on hemodialysis. The remaining 23.1% who did not undergo nephrectomy demonstrated acceptable graft function. Figure. No caption available. Figure. No caption available. Figure. No caption available. Conclusion: This is the largest single center study in commercial RTX reporting the highest number of patients with IFI acquired over a relatively short period of time. Aspergillus spps were the main culprit fungi with no Candida spps being isolated. A high index of suspicion might be the most reasonable mean to reduce the possible grim outcome. Improving legal transplant programs and strengthening the legal laws can prevent commercial transplant tourism.